Computational approach to explore the inhibitory potential of biologically derived compounds against Spodoptera litura vitellogenin receptor (VgR) using structure based virtual screening and molecular dynamics. Issue 11 (28th June 2022) - Aathmanathan, Veeranarayanan Surya; Arumugam, Velusamy; Krishnan, Muthukalingan
Abstract: In the everlasting combat against the pests of agricultural importance, it is essential to come up with a novel strategy for pest control. This can be achieved through understanding the insect pest at cellular and molecular levels. Vitellogenin (Vg) and vitellogenin receptor (VgR) are essential for successful reproduction in insect. The N-terminal Ligand Binding Domain (LBD) of VgR is responsible for the transportation of vital protein (Vg) to the developing oocyte through receptor mediated endocytosis pathway. This can be implemented to various predicaments and betterments for exploitation in pest management, in a target specific and eco-friendly manner. For this, natural metabolites isolated from various biological sources were used as ligand. The purpose of this study was to analyze the inhibitory potential of 14 biologically derived compounds against N-terminal (Ligand Binding Repeats) LBRs of S. litura by computational docking. 3 D structure of LBRs of S. litura was generated by Raptor X software and the structure was refined and validated. The validated structure was docked using autodock vina. Docking results revealed that spinosyn A and milbemycin A4 have inhibitory activity against VgR. Molecular dynamics (MD) simulation confirms the stable binding of the ligand. From the above results, spinosyn A and milbemycin A4 may be exploited for the pest management. Communicated by Ramaswamy H. Sarma